Analysis of Containment Theory on Drug Abuse in a Drug Prone Subcultural Environment : A Study Case of Kampung Muara Bahari - Najla, Darin Hana Majid Labibah; Zaky, Muhammad (Dinasti Research, 2025)
This research discusses the phenomenon of drug abuse in a drug-prone subculture environment, namely in Kampung Muara Bahari. Subculture values and norms in Kampung Muara Bahari influence individual decisions that affect their self-restraint. The purpose of this research is to analyze the factors that can attract or encourage individuals which lead them to be involved in drug abuse in Kampung Muara Bahari. Viewed through the perspective of Criminology Containment Theory, this research uses a descriptive qualitative approach through data collection techniques with non-participatory observation, semi-structured interviews, and literature study. This research has informants as many as three buyers and drug abusers in Kampung Muara Bahari, one victim, and one North Jakarta BNN staff member. The results showed that the perpetrators were involved in drug abuse because of their weak self-restraint factor so that the perpetrators could easily get involved in illegal drug activities. This phenomenon shows that the perpetrators have weak self-restraint due to the absence of a strong self- concept, material-oriented and short-term goals, subculture, low tolerance for frustration, peer groups, neglect of values and norms to weak supervision in the Kampung Muara Bahari environment.